MYRF-related mild encephalopathy with reversible myelin vacuolization: a case report and literature review - Yao, Shumei; Mo, Xiufeng; Luo, Changjiang; Qu, Chuanqiang (Frontiers in Genetics, 2023)
Background:MYRF-related mild encephalopathy with reversible myelin vacuolization (MMERV) is an inherited neurological disorder characterized by dysfunction in the central nervous system and widespread reversible leukoencephalopathy. This paper presents a confirmed case of familial MMERV and summarizes pertinent features to offer guidance for future diagnosis and treatment of MMERV. Case Introduction: We have diagnosed a case of MMERV based on a history of seizures during early childhood and recurrent speech fluency issues in adulthood, reversible abnormal intensities in bilateral white matter in the centrum semiovale and corpus callosum, and the identification of myelin regulatory factor (MYRF) heterozygous variants. Conclusion:MYRF-related mild encephalopathy with reversible myelin vacuolization is a rare autosomal dominant genetic disease, with early clinical manifestations often being seizures. The definitive diagnosis of MMERV can be confirmed through genetic analysis. Minimizing infections can help reduce disease recurrence. However, future research should explore the impact of MYRF heterozygous variants in the wider MMERV population.